Digital twin simulations with a micro-multiphysics agent-based model reveal key drivers of bone loss after denosumab discontinuation - Ledoux, Charles; Kendall, Jack J.; Boaretti, Daniele; Müller, Ralph; Collins, Caitlyn J. (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundDenosumab is a widely used pharmacological treatment for osteoporosis-related bone fragility; however, its discontinuation is followed by a rapid drop in bone density.MethodsWe investigate proposed mechanistic hypotheses from literature for this rapid bone loss using a computational micro-multiphysics agent-based model validated against clinical data. Using a representative selection of iliac crest patient biopsies scanned with micro-computed tomography, this model generates digital twin simulations of denosumab discontinuation after various treatment periods, with ceteris paribus implementations of each mechanistic hypothesis.ResultsOur mixed effects linear regression analysis suggests that only the gate-blocking effect (p=0.014) and osteomorphs recycling (p=0.007) explain the rapid bone loss post denosumab discontinuation. In silico cell and cytokine dynamics emphasize that fusion of osteomorphs is more rapid than osteoclast precursor differentiation in the short-term.ConclusionThese findings highlight potential targets for managing fracture risk when discontinuing denosumab and emphasize the importance of personalized treatment strategies based on high-resolution imaging in addition to bone turnover marker measurements.